CUSTOMER RESPONSE INDEX (CRI): PENGUKURAN EFEKTIVITAS IKLAN SMARTPHONE VIVO V7+ AGNES MONICA: CUSTOMER RESPONSE INDEX (CRI): PENGUKURAN EFEKTIVITAS IKLAN SMARTPHONE VIVO V7+ AGNES MONICA - Sastika, Widya; Wulandari, Astri; Hanifa, Fanni Husnul (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2018)
ABSTRACTOne of the media use by company to introduce their products to consumers is by television. Advertiseon TV media is more expensive but is well-targeted than other media. Vivo smartphones as a largephone company from China spent Rp 830 billion for advertising, by launching one of the Vivo smartphones series that was carried out simultaneously on nine national televisions wtih singer AgnezMonica as brand ambasador. The value of Vivo smartphone ad shopping is so big with a 577%increase in 2017 compared to 2016, it is expected that Vivo smartphone sales will also increase. Thepurpose of this study was to determine the effectiveness of Vivo V7 + Agnes Monica ads on televisionmedia with the Customer Response index (CRI) method. Dimensions of the Customer Response Index(CRI) consist of awareness, understanding, interest, intentions and actions. Respondents in this studywere conducted by distributing questionnaires to 100 respondents in the city of Bandung. The studyuse in this research methods is quantitative and descriptive methods. The results of data processingthe percentage value of Customer Response Index (CRI) is 67.01% greater than the value of unwarepercentage 0%, no comprehend 13%, no interest 7.83%, no intention 3.92% and action number 8.24%. So, it can be concluded that the Vivo V7 + Agnes Monica advertisement on television is effective.